Strategic interventions and a novel model for the integration of community pharmacy and primary care in Spain: qualitative insights - Victoria Garcia-Cardenas; Miguel A Gastelurrutia; Celia Piquer-Martinez; Amaia Urionagüena; Shalom I. Benrimoj; Begoña Calvo; Noelia Amador-Fernandez; Fernando Martinez Martinez (BMJ Open)
Objectives To explore the opinions and perceptions of key stakeholders on the integration between community pharmacy and primary care, within the Valencian Autonomous Community. Specific objectives include identifying strategic interventions to facilitate this integration. Additionally, the manuscript discusses the formulation of a novel model for the integration of community pharmacy and primary care.Design Qualitative, with data from five virtual focus groups (FG) and 12 semistructured interviews analysed thematically using NVivo and interventions prioritised through a virtual nominal group technique.Setting Valencian Autonomous Community (Spain).Participants FG involved community pharmacists (CP) and primary care stakeholders including general practitioners, primary care nurses, general practitioner pharmacists, social services managers and administrators. Interviewees were government representatives and professionals from organisations. Selection was through snowball sampling and invitations by Official Colleges of Pharmacists.Results Five themes emerged, revealing the multifaceted nature of integrating community pharmacies and primary care. ‘Integration’ was identified as an ambitious target, anchored in collaboration and communication efforts. The role of CP was particularly noted for their direct patient interaction and trust, vital in fostering medication adherence. Barriers like role ambiguity and regulatory environment were highlighted. Seven interventions were identified to enable integration, with three of them prioritised: ‘bidirectional communication’, ‘protocol standardisation’ and ‘multidisciplinary team strengthening’. These interventions, linked with prior components of health system integration, led to a pioneer integration model.Conclusions Recognising stakeholder insights is essential in shaping workable, practical and adaptable models for integration. Tailoring these temporal models to stakeholders' immediate needs and strategic priorities may serve as effective starting points for integration. Support from professional bodies and proactive stakeholders’ engagement will optimise the integration success and its acceptance across healthcare levels.